In Silico Evaluation of Natural Compounds as Dual Inhibitors of Exotoxin A and LasB (Elastase) Virulence Proteins in Pseudomonas aeruginosa - Andrias Bayu Fariska; Linda Erlina; Ade Arsianti; Aryo Tedjo (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Pseudomonas aeruginosa is an opportunistic pathogen whose virulence is largely mediated by Exotoxin A and LasB (elastase), making them promising anti-virulence drug targets. This study aimed to evaluate the inhibitory potential of natural compounds against these two key proteins using an in silico approach. Pharmacophore-based virtual screening of HerbalDB compounds was performed by LigandScout software, followed by molecular docking using AutoDockTools-1.5.7 against Exotoxin A (PDB ID: 1AER) and LasB (PDB ID: 1U4G). Native ligands and co-crystallized inhibitors were used as docking controls to validate binding accuracy. Among the screened compounds, Epicatechin-(4β-6)-epicatechin-(4β-8)-catechin exhibited the strongest binding affinity to Exotoxin A (ΔG = −10.72 kcal·mol⁻¹), while Carpaine showed the highest affinity for LasB (ΔG = −8.91 kcal·mol⁻¹). The predicted interactions involved hydrogen bonds and hydrophobic interactions with active-site residues, comparable to the native inhibitors. Furthermore, ADMET analysis indicated favorable pharmacokinetic and drug-likeness properties. These findings suggest that selected natural compounds possess potential dual inhibitory activity against Exotoxin A and LasB, warranting further experimental validation as anti-virulence candidates for controlling P. aeruginosa infections.